Quantitative Estimate of the Resonance Effects in Some Unsaturated, Monocyclic, and Aromatic Hydrocarbons Based on the Renewed Optical Exaltations - Zaitsev, Boris A. (Current Organic Chemistry, 2022)
The present review discusses a new viewpoint on refractometry as the oldest experimental physical method, whose scientific potential in the estimation of structural effects in organic chemistry has been missed so far. The author demonstrates that upon certain adjustment and redesign of refractometry, this potential can be tapped and successfully used to determine a type of π-electron interaction, delocalization degree of π-electrons in organic compounds, and to perform quantitative estimates of resonance effects in unsaturated, (polycyclic) aromatic, and other polyconjugated systems (e.g., fullerenes). The method for accurate separation of molar refraction into additive and constitutive components was suggested; the method is based on the specially developed additive scheme. It was revealed that the negative deviations from additivity for cycloalkanes depend linearly on the number of carbon atoms in the ring. Excellent linear correlations between renewed optical exaltations, the number of π-electrons in a conjugated system, and experimentally found resonance energy (determined from hydrogenation heat values) were demonstrated. Angular coefficients of the correlation series (ρ-constants) are considered as a criterion of classification, which characterizes the degree of mobility of π-electrons in the conjugated system of a given type. It is emphasized that the development of methods for precise measurement of the constitutive components of molar refraction may become a useful additional source of information about resonance and other effects in organic and polymer chemistry.
Keywords: quantitative estimation